Development of advanced air-blown entrained-flow two-stage bituminous coal IGCC gasifier - Abaimov Nikolay A.; Ryzhkov Alexander F. (EPJ Web of Conferences, 2017)
Integrated gasification combined cycle (IGCC) technology has two main advantages: high efficiency, and low levels of harmful emissions. Key element of IGCC is gasifier, which converts solid fuel into a combustible synthesis gas. One of the most promising gasifiers is air-blown entrained-flow two-stage bituminous coal gasifier developed by Mitsubishi Heavy Industries (MHI). The most obvious way to develop advanced gasifier is improvement of commercial-scale 1700 t/d MHI gasifier using the computational fluid dynamics (CFD) method. Modernization of commercial-scale 1700 t/d MHI gasifier is made by changing the regime parameters in order to improve its cold gas efficiency (CGE) and environmental performance, namely H2/CO ratio. The first change is supply of high temperature (900°C) steam in gasifier second stage. And the second change is additional heating of blast air to 900°C.